2021
DOI: 10.1002/anie.202108684
|View full text |Cite
|
Sign up to set email alerts
|

Arylamine‐Linked 2D Covalent Organic Frameworks for Efficient Pseudocapacitive Energy Storage

Abstract: The development of new linkages is one of the most efficient strategies to enrich the diversity of covalent organic frameworks (COFs). Particularly, functional linkages can endow COFs with additional tailored properties besides the building units, which further diversify COFs with desirable functions. Herein, we have developed a new arylamine linkage for the construction of COFs. Two new arylamine‐linked COFs (AAm‐TPB and AAm‐Py) were prepared by condensing cost‐effective dimethyl succinyl succinate (DMSS) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
87
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 81 publications
1
87
0
2
Order By: Relevance
“…32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium. 59,60 However, due to the face to face lamellar stacking, the active sites in the layers of 2D COFs cannot be fully exposed to electrolytes and CO 2 , which usually leads to low activity and current density.…”
Section: Introductionmentioning
confidence: 99%
“…32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium. 59,60 However, due to the face to face lamellar stacking, the active sites in the layers of 2D COFs cannot be fully exposed to electrolytes and CO 2 , which usually leads to low activity and current density.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these factors, we intend to employ porous organic polymers (POPs) 24 , 25 , with porous aromatic framework (PAF) as the representative 26 , as a platform to construct PFAS adsorbent due to their advantageous features of ultrahigh surface areas (>5600 m 2 g −1 ), adjustable framework structures, tunable pore sizes, readily functionalized pore wall, and exceptional water/chemical stabilities 27 29 . These POPs have been previously applied in the fields of gas storage and separation 30 , 31 , proton conduction 32 , 33 , catalysis 34 , 35 , energy storage 36 , 37 , enzymatic immobilization 38 , 39 , and water treatment 40 , 41 . Herein, we describe a synergistic binding sites protocol to construct PFAS adsorbent by simultaneously introducing electrostatic and hydrophobic sites onto POPs as adsorption sites (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] COFs have displayed excellent performance in many different fields such as gas/molecular separation, chemical sensors, ionic conduction, and electrochemical energy storage and conversion systems because of their designable skeletons and porosities as well as stable frameworks. [ 7–9 ] In addition, different atoms are periodically and uniformly distributed on the skeletons of COFs, which made them the ideal precursors of functional carbons for applications in lithium‐ion batteries, supercapacitors, and electrocatalysts. [ 10 ] Recently, COFs‐derived carbon has been utilized as a support to anchor metal atoms.…”
Section: Introductionmentioning
confidence: 99%